Predicting Student Intention to Wear a Mask to Avoid Contracting COVID-19. (September 2021) - Zahed, Karim; Arthur, Kianna; Engler, Solangia; Sasangohar, Farzan; Smallman, Rachel; Fields, Sherecce
With governments having enforced mask mandates and stressing the importance of wearing masks to avoid contracting COVID-19, still many individuals do not properly adhere to recommended guidelines. To investigate factors influencing why individuals engage in wearing masks, 578 participants at a university in the southern United States completed a survey, answering questions related to various behavioral change theories, including the Health Belief Model, the Theory of Planned Behavior, and the Transtheoretical Model. Intention was rated high and was positively correlated with Subjective Norms and Self Efficacy . However perceived benefits of wearing a mask and perceived susceptibility were rated low indicating that benefits and susceptibility did not influence intention. The SEM model showed that benefits actually had a negative relationship with intention, whereas susceptibility had no significant relationship. Integrating constructs from the Health Belief Model and the Theory of Planned Behavior increased variance predicted of Intention to wear a mask to 56%.